Symptoms of Heat Stress in Farm Animals and Negative Effects on Growth and Milk Production - Mostafa Habeeb, Alsaied Alnaimy (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
Optimal climatic conditions for cattle, buffaloes, sheep goats, rabbits and poultry would be something like an air temperature of 13 to 20ºC, a wind velocity of 5 to 18 km/hr., relative humidity of 55 to 65% and a moderate level of sunshine and these factors are interrelated. In tropical and subtropical countries, the climatic characteristic is the major constraint on animal productivity. The summer in Egypt is characterized by high ambient temperature, intense solar radiation and high relative humidity. Therefore, farm animals are raised to such severe climatic stress for almost 6 months of the year. Growth, milk production and reproduction are impaired by about 50% as a result of the drastic changes in biological functions caused by heat stress which include a decrease in feed intake, feed efficiency and utilization, disturbances in water, protein, energy and mineral balances, enzymatic activities, hormonal secretions and blood metabolites ending to impairment the productive and reproductive performance.